2016
DOI: 10.13164/re.2016.0652
|View full text |Cite
|
Sign up to set email alerts
|

Average Polarization of Electromagnetic Gaussian Schell-Model Beams through Anisotropic Non-Kolmogorov Turbulence

Abstract: Abstract. Polarization properties of electromagnetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results indicate that the behavior of the degree of polarization depends on the statistical properties of the source generating the EGSM beams and the parameters of the cavity. Zhao Yuanhang [8] studied the polarization properties of electromagnetic Gaussian Schell-model beams propagating through the anisotropic non-Kolmogorov turbulence of a marine-atmosphere channel based on the cross-spectral density matrix of the beam. The electromagnetic Gaussian Schell-model beam with smaller δyy, δxx, and Ax parameters, but a larger Ay, will reduce the interference of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the behavior of the degree of polarization depends on the statistical properties of the source generating the EGSM beams and the parameters of the cavity. Zhao Yuanhang [8] studied the polarization properties of electromagnetic Gaussian Schell-model beams propagating through the anisotropic non-Kolmogorov turbulence of a marine-atmosphere channel based on the cross-spectral density matrix of the beam. The electromagnetic Gaussian Schell-model beam with smaller δyy, δxx, and Ax parameters, but a larger Ay, will reduce the interference of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies investigating anisotropy characteristics of the turbulent spectrum in different media [17][18][19][20] . These studies [17][18][19][20] cover the log-amplitude correlation function for spherical wave propagation through anisotropic non-Kolmogorov atmosphere, average polarization of the electromagnetic Gaussian Schell model beams propagating through anisotropic non-Kolmogorov turbulence, polarization of quantization Gaussian Schell beams through anisotropic non-Kolmogorov turbulence of the marine atmosphere, and effects of anisotropic turbulence on the average polarizability of Gaussian Schell model quantized beams through an ocean link. In our earlier studies, we have reported in anisotropic oceanic turbulence, the intensity fluctuations of spherical optical beams [21] , the intensity fluctuations [22] , and the bit error rate (BER) of asymmetrical Gaussian beams [23] .…”
mentioning
confidence: 99%